Предмет: Алгебра,
автор: kryto23
решить функцию 4(х-2)-3(у+3)=1 3(х+2)-2(х-у)=5
Ответы
Автор ответа:
0
{4(х-2)-3(у+3)=1
{3(х+2)-2(х-у)=5
{4x - 8 - 3y - 9 = 1
{3x + 6 - 2x + 2y = 5
{4x - 3y = 18
{x + 2y = -1
{4x - 3y = 18
{x = -1 - 2y
{-4 - 8y - 3y = 18
{x = -1 - 2y
{-11y = 22
{x = -1 - 2y
{y = -2
{x = -1 -2y
{y = -2
{x = 3
{3(х+2)-2(х-у)=5
{4x - 8 - 3y - 9 = 1
{3x + 6 - 2x + 2y = 5
{4x - 3y = 18
{x + 2y = -1
{4x - 3y = 18
{x = -1 - 2y
{-4 - 8y - 3y = 18
{x = -1 - 2y
{-11y = 22
{x = -1 - 2y
{y = -2
{x = -1 -2y
{y = -2
{x = 3
Автор ответа:
0
4X - 8 - 3Y - 9 = 1 ---> 4X - 3Y = 18
3X + 6 - 2X + 2Y = 5 --> X + 2Y = - 1 ---> ( -4X - 8Y = 4)
- 11Y = 22 ---> Y = (- 2)
4X + 6 = 18 ---> 4X = 12 ---> X = 3
ОТВЕТ: Х = 3 Y = ( - 2)
3X + 6 - 2X + 2Y = 5 --> X + 2Y = - 1 ---> ( -4X - 8Y = 4)
- 11Y = 22 ---> Y = (- 2)
4X + 6 = 18 ---> 4X = 12 ---> X = 3
ОТВЕТ: Х = 3 Y = ( - 2)
Похожие вопросы
Предмет: Другие предметы,
автор: abereznenko8
Предмет: Алгебра,
автор: veroni4kaevtushenko
Предмет: История,
автор: Аноним
Предмет: Литература,
автор: hjshjgdgj
Предмет: Алгебра,
автор: Лиза1001